A Failure of Process? Comprehending the Issues Fostering Heritage Conflict in Dresden Elbe Valley and Liverpool — Maritime Mercantile City World Heritage Sites. (May 2015) - Gaillard, Bénédicte; Rodwell, Dennis
<x content-type="archive" xml:space="preserve">Abstract</x> The acceleration of development pressures in recent decades has focused attention on the spectrum of major challenges facing the diverse stakeholders charged with the safeguarding and protection of World Heritage Sites. This paper compares two sites that have highlighted these challenges, both of which were inscribed on the United Nations Educational, Scientific, and Cultural Organization (UNESCO) World Heritage List in 2004: Dresden Elbe Valley, Federal Republic of Germany, placed on the World Heritage List in Danger in 2006 and delisted in 2009; and Liverpool — Maritime Mercantile City, UK, placed on the World Heritage List in Danger in 2012 and the subject of ongoing debate. The paper questions inconsistencies in the decision-making processes that may have triggered conflicts of interest in these two cases, positions the developing UNESCO concept of historic urban landscape as an enabler of integrative urban development, and draws lessons for the implementation of the World Heritage Convention.